Forced migration and internally displaced persons: Latin America and Europe - Bijos, Leila (2016)
The aim of this research is to analyze immigration and internal displacement focusing on human rights. The analysis will concentrate on conflict induced internal displacement, causes of internal displacement due to environment change, natural disasters, which are in mostof the cases interlinked with political conflicts, causing the forced movement of families .This is an empirical research which critically will examine the changing dynamics of forced displacement and the challenges faced by affected states and the international community.More specifically, it analyzes key developments in immigration policy and practice; it re-examines the contemporary scenario around durable solutions in a context of policy issues related to internally displaced persons and stateless population.